PENGARUH MODAL KERJA TERHADAP PENDAPATAN UMKM KEBAB DAN BURGER FETIH TURKI JAMBI - Hidayat , Ma'ruf; Sissah, Sissah; Hafiz, Ahsan Putra (Program Studi Manajemen Keuangan Syariah, 2024)
This study aims to determine the effect of working capital on the income of UMKM Kebabsand Fetih Turki Jambi Burgers and to find out how working capital influences the income of UMKM Kebabs and Fetih Turki Jambi Burgers. The type of research applied to this research is quantitative research with a descriptive approach. Qualitative research is a broad type of research. Descriptive research is a research method used to find the widest possible knowledge of the object of research at a certain time. the effect of working capital on the income of UMKM Kebab and Burger Fetih Turki Jambi has a positive linear effect but does not have a significant effect. The type of data used is secondary data, namely data that has been processed by the MSME in question in the form of an annual report. The period used as an annual research is for five years starting from 2016 to 2020. Based on the results of the research that has been done, obtained simple linear regression analysis data and also tested statistically the effect of working capital on the income of UMKM Kebab and Burger Fetih Turki Jambi period January 2016 â€“ December 2020 has a positive linear effect but no significant effect. With a positive correlation coefficient value of 0.437, which means that the relationship between working capital and the income of UMKM Kebab and Burger Fetih Turki Jambi is positively related (unidirectional) but not significant, by looking at the determination test only 19.1% and still 80.9% factor- factors that influence significantly that are not involved in this study.Â Â